THE PROCESS'S "TECHNICAL DIAGNOSIS" EFFECTIVENESS AND EFFICIENCY DEFINING - S.M. KHARAKHASHYAN; K.L. KHUBIYAN; V.P. DIMITROV (Advanced Engineering Research, 2009)
The macroprocess's decomposition of the combine exploitation is carried out. The indexes and the process's «technical diagnosis» effectiveness and efficiency defining method are offered. The offering method's practical using data is adduced.